Advanced Parallel Processing Technologies 9th International Symposium, APPT 2011, Shanghai, China, September 26-27, 2011. Proceedings - Temam, Olivier; Yew, Pen-Chung.; Zang, Binyu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 9th International Symposium on Advanced Parallel Processing Technologies, APPT 2011, held in Shanghai, China, in September 2011. The 13 revised full papers presented were carefully reviewed and selected from 40 submissions. The papers are organized in topical sections on parallel distributed system architectures, architecture, parallel application and software, distributed and cloud computing.
Keywords: Computer science; Operating systems (Computers).; Database management; Data mining; Information storage and retrieval systems; Computer Science; Database Management; Data Mining and Knowledge Discovery; Information Systems Applications (incl. Internet).; Operating Systems; Programming Techniques; Information Storage and Retrieval